2007
DOI: 10.1016/j.trf.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in preschool children’s declared and behavioral compliance with pedestrian rules

Abstract: The study examined gender differences in compliance with pedestrian rules among preschool children. Two groups of 5-year-old boys and girls containing a total of 162 children participated in the study. First, the children's compliance was assessed during crossing and walking by observing their pedestrian behaviors. Then, each child was interviewed on pedestrian-danger appraisal, rule knowledge, rule compliance, and rule internalization. As hypothesized, the results showed that girls' behaviors were more compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
2
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 49 publications
(69 reference statements)
8
25
2
12
Order By: Relevance
“…19 For example, some studies have found that women show more tax compliance than men (see Kastlunger et al 2010), they are less likely to engage in drink-driving (Scott-Parker et al 2014) and among pedestrians, males violate more rules than females (Tom and Granié 2011), already at young age (Granié 2007). 20 We would like to thank two anonymous referees for suggesting these further checks.…”
Section: Robustness Checksmentioning
confidence: 98%
“…19 For example, some studies have found that women show more tax compliance than men (see Kastlunger et al 2010), they are less likely to engage in drink-driving (Scott-Parker et al 2014) and among pedestrians, males violate more rules than females (Tom and Granié 2011), already at young age (Granié 2007). 20 We would like to thank two anonymous referees for suggesting these further checks.…”
Section: Robustness Checksmentioning
confidence: 98%
“…Les recherches actuelles sur l'éducation routière de l'enfant piéton distinguent quatre compétences impliquées dans la tâche de traversée, toutes relevant principalement du traitement de l'information en situation de résolution de problème (Thomson, Tolmie, Foot et Mc Laren, 1996) : choisir un bon site de traversée (Tabibi et Pfeffer, 2003, 2007, analyser la situation routière (Whitebread et Neilson, 2000), estimer les espaces intervéhiculaires (Oxley, Ihsen, Fildes, Charlton et Day, 2005) et anticiper le comportement des conducteurs (Foot, Thomson, Tolmie, Whelan, Morrison et Sarvary, 2006). Ces travaux permettent de dégager les processus cognitifs à l'oeuvre dans la tâche de traversée : prise de point de vue perceptive d'autrui (Demetre et Gaffin, 1994), attention sélective et recherche visuelle (Thomson et al, 1996), traitement de l'information et division de l'attention (Guttentag, 1984), perception des distances, des vitesses et temps au contact (Demetre, Lee, Pitcairn, Grieve, Thomson et AmpofoBoateng, 1992).…”
Section: Approche Cognitivisteunclassified
“…Des travaux récents sur l'enfant piéton ont montré que les enfants de cinq ans qui ont des comportements plus contrôlés dans la rue sont en même temps ceux qui ont une internalisation plus importante des règles routières (Granié, 2007). La plus grande conformité de certains enfants aux règles routières -observée dans leur comportement quotidien de déplacement accompagné -s'expliquerait par une plus grande internalisation de ces règles à leur système de valeurs personnel, qui engendrerait à son tour un meilleur autocontrôle de leur comportement dans l'espace urbain.…”
Section: Internalisation Et Autocontrôle Comportemental Chez L'enfantunclassified
See 1 more Smart Citation
“…Granié, 2004b) qui varient en fonction de son âge, de son sexe, du contexte social et physique de son activité et qui vont agir sur les choix décisionnels et sur les comportements qu'il met en place en tant que piéton (M.-A. Granié, 2007 ;Holland & Hill, 2007 ;Moyano Diaz, 2002 ;A. K. Tolmie et al, 2006 ;Yagil, 2000).…”
unclassified